Pathology, multimodal imaging and clinical significance of age-related fundus deposits - CAI Jinyu; JIANG Yanmei; CHEN Ling (Yanke Xuebao)
Fundus aging is a key factor and pathological basis for the development and progression of age-related macular degeneration (AMD), which is histopathologically characterized by choroidal capillary atrophy, Bruch’s membrane(BrM) thickening, and abnormalities of retinal pigment epithelium (RPE). BrM thickening can be induced by the aggregation of age-related fundus deposits and plays an essential role in the pathogenesis of AMD. Basal laminar deposits (BLamD) represent diffuse thickening of the basement membrane of RPE, usually considered to be a normal fundus aging. Basal linear deposits (BLinD) and soft drusen, mainly composed of neutral lipids such as esterified and unesterified cholesterol, can disrupt the homeostasis of material exchange between the choroid and the outer retina, resulting in ischemia, hypoxia, and oxidative stress in the outer retina, which are important pathological changes in the early AMD. Hard drusen is mainly distributed in the peripheral retina and is very common in aging fundus; Cuticular drusen are resulted from focal nodular thickening of the basement membrane of RPE, with similar appearance as hard drusen, but mainly distributed in the posterior pole and more numerous and denser. Recently, our understanding of subretinal drusenoid deposits (SDD), deposits above the RPE, has been gradually deepened and it also has profound significance in the pathogenesis of AMD. In this review, we presented the pathologic features and multimodal imaging of age-related fundus deposits (including hard drusen and cuticular drusen), aiming to help recognize and understand the manifestations, pathologic features, and formation mechanisms of these deposits, as well as their clinical significance in the development and progression of AMD.